Australian Coal Theatrics. Issue 1 (March 2023) - Varney, Denise; Stevens, Lara
Abstract : Climate change was the defining issue in the 2022 Australian federal election. As a new administration takes power, all sectors, including the performing arts, need to keep up the pressure. An iconic moment of "coal theatrics" in Parliament House, so labeled by the Australian media, stands in contrast to artistic performances that continue to put pressure on the framers of political and cultural policy.